Practical training report: Syariah Judiciary Deparment Of Sarawak / Nur Sahirah Asman - Asman, Nur Sahirah (University Technology MARA Sarawak, 2018)
The Sarawak Malay Court has been in charge of family affairs under the Sarawak Malay Courts Act 1915 and the amendments 1956. However, there were some weakness in that laws. In 1978. the Syariah Court was established under the Sarawak Islamic Council Law (Incorporation). On March 1, 1985 the Order’s Law was enforced. As in Sarawak, due to some concerned from the Sarawak State Government to enhancing Islam’s position and dignity, the Syariah Court has been separated from its Islamic administration. On October 2, 1990, the Syariah Judiciary Department of Sarawak (JKSS) was established. On May 14, 1991, the Sarawak State Government had approved 6 bills includes Syariah Court Ordinance, Criminal Event Ordinance, Mal Event Ordinance, Syariah Criminal Offenses Ordinance, Islamic Family Law Ordinance, Islamic Legal Information Ordinance. In addition, on September 1,1992, the six ordinances were gazetted. The 1997 Ordinance were amended on December 27, 2001 and have been effectively use from December 1st, 2004.